PENGARUH KARAKTERISTIK RUMAH TANGGA DESA DAN KOTA TERHADAP ALOKASI WAKTU ANAK UNTUK BEKERJA DI INDONESIA - Purwanti, Putu Ayu Pramitha (PIRAMIDA, 2014)
The aim of this study to analyze the effect of household characteristics in Indonesia on child activities to work and school. Tendency to work and school are estimated by OLS and logit models using IFLS data 2000 and 2007. The estimation results prove that there is difference between boys and girls on child’s decision to work or school. These two activities are also influenced by gender of household head, parental education and income. Location of residence only affect the intensity of working children and not children’s education.
Keywords: household characteristics; work; school